2000
DOI: 10.1097/00005176-200001000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Randomized Controlled Trial of Glutamine-Enriched Polymeric Diet in the Treatment of Active Crohn's Disease

Abstract: The findings suggest that a glutamine-enriched polymeric diet offers no advantage over a standard low-glutamine polymeric diet in the treatment of active Crohn's disease. Rather, it appears to be less effective in improving PCDAI. The reported beneficial effects of glutamine seen in many catabolic states must be viewed with caution when extrapolating to the management of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 27 publications
0
95
0
12
Order By: Relevance
“…Two published human studies on enteral glutamine supplementation in patients with Crohn's disease included a total number of 32 patients (14 adults, 18 children) (Den Hond et al, 1999;Akobeng et al, 2000). Neither study observed an effect of enteral glutamine supplementation (over a 4-week period) on intestinal permeability or inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two published human studies on enteral glutamine supplementation in patients with Crohn's disease included a total number of 32 patients (14 adults, 18 children) (Den Hond et al, 1999;Akobeng et al, 2000). Neither study observed an effect of enteral glutamine supplementation (over a 4-week period) on intestinal permeability or inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data supporting this assumption are rare. Only two studies have been published in which gln was administered by an enteral route in 18 and 14 IBD patients (Den Hond et al, 1999;Akobeng et al, 2000). This means that data are only available for 16 IBD patients treated with gln.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tak więc ESPEN nie zaleca stosowania glutaminy u pacjentów z tymi chorobami [35,36]. Wyniki dwóch badań z randomizacją nie wykazały korzystnego wpływu dojelitowego żywienia z glutaminą w porównaniu z żywieniem standardowym lub placebo na aktywność choroby Leśniowskiego-Crohna oraz na parametry kliniczne i antropometryczne [37,38]. Akobeng i wsp.…”
Section: Nieswoiste Choroby Zapalne Jelitunclassified
“…Akobeng i wsp. [37] wykazali w grupie 18 pacjentów z chorobą Leśniowskiego-Crohna, że dieta polimeryczna z 42-procentową zawartością glutaminy w stosunku do 4-procentowej zawartości tego aminokwasu nie wpływała istotnie na poziom kwaśnej globuliny osocza, liczbę płytek krwi i masę ciała. Den Hond i wsp.…”
Section: Nieswoiste Choroby Zapalne Jelitunclassified